Efektivitas Promosi Melalui Radio Terhadap Kepatuhan Para Muzakki di Surabaya - Fadillah, Firda Nur; Widiastuti, Tika (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
This study aims to determine the effectiveness promotion through radio to obedience of muzakki channelling zakat at the zakat institute in Surabaya. This research is qualitative. The approach in this study using case study strategy. Characteristics of the informants in this study is muzakki distribute their zakat to zakat institutions in Surabaya and ever listen promotion of zakat institutions through radio. Informants in this study amounted to 9 muzakki. Technical data collection is done by using the interview method. After the data collected do data reduction, data presentation and conclusion (verification). The results showed that the promotion through radio by zakat institution in Surabaya improving obedience muzakki said to be effective. Effectiveness is measured by three indicators, there are muzakki understanding of zakat, zakat practice frequency, and amount of donation.